SUBTYPE CHARACTERICS OF DENDRITIC CELLS FROM PERIPHERAL BLOOD OF PATIENTS WITH RHEUMATOID ARTHRITIS - S. A. Falaleeva; V. V. Kurilin; N. S. Shkaruba; O. A. Chumasova; A. E. Sizikov; S. V. Sennikov (Медицинская иммунология)
Abstract. Characteristics of myeloid and plasmacytoid dendritic cells from peripheral blood were studied in healthy donors and patients with rheumatoid arthritis (RA). We evaluated relative amounts of dendritic cell by their subtypes, degree of their maturity, and ability to respond to the maturation factors (toll-like receptor 4, 7 and 8 agonists). The results of in vitro experiments have shown that the patients with rheumatoid arthritis exhibited a significant reduction in numbers of plasmacytoid dendritic cells from peripheral blood. A sufficient decrease in CD83, CD80 expression on dendritic cell subtypes in RA patients was significantly less, than in healthy donors. In patients with RA, a significant increase in the number of CCR7-expressing plasmacytoid dendritic cells was shown in peripheral blood. In stimulated cultures, maturation of dendritic cells expressing maturation markers (CD83, CD80, CCR7) proved to be increased up to normal values. It should be noted that the counts of plasmacytoid dendritic cells in peripheral blood of RA patients expressing CCR7 was significantly higher than among healthy donors. Meanwhile, expression of CD83 and CD80 increased tovalues of healthy donors.Hence, we have found a significant reduction in relative counts of blood-derived myeloid and plasmacytoid dendritic cells expressing markers of mature dendritic cells (CD83, CD80) in patients with rheumatoid arthritis. Upon stimulated in vitro maturation, the counts of myeloid and plasmacytoid dendritic cells expressing CD83 and CD80 increased to the values corresponding to those of control group. RA patients showed significantly higher numbers of plasmacytoid dendritic cells expressing CCR7. This could indicate some changes in functional activity of dendritic cells in peripheral blood of patients with RA.